Uso de diferentes fitofisionomias por macacos-prego-do-peito-amarelo Sapajus xanthosternos Wied-Neuwied 1820 em fragmento de Mata Atlântica, Sergipe, Brasil - Sousa, Saulo Meneses Silvestre de (2016)
Capuchin monkeys are frugivorous-insectivorous primates, although they can explore a wide range of food items. The availability of fruits is a key-aspect of the ecology of these primates, with direct influences over the quality of a given area for the species, and often represents the main determinant of the pattern of range use of groups. In a population-level analysis, however, the pattern of occupation of a fragment by capuchin monkeys is influenced by a broader set of factors, including structural parameters of the habitat. The purpose of this study was to describe the pattern of use of different phytophysiognomies by a population of yellow-breasted capuchins in an Atlantic Forest fragment, relating to the structural aspects and fruit availability of the environment. The study area is in Itaporanga D'Ajuda (11º08'07 "S, 37º18'43" W), in the state of Sergipe, henceforth denoted by Fazenda Rio Fundo (FRF). The fragment has approximately 800 ha of native forest, associated with surrounding plantations of Eucalyptus sp. and bamboos. Among the native forest formations, the vegetation types of shrub-arboreal Restinga (RE), Mata de Tabuleiro (MT), and arboreal Restinga (mature, FM, and secondary, FS). Data collection was carried out monthly between March 2015 and February 2016. The different habitat types of the FRF were compared in relation to the availability of fruits, through phenological monitoring of tree species; and habitat structure, by analyzing its medium height, DBH, density, land cover rate and species composition of the tree community. The use of different habitats by capuchin monkeys, and the occurrence of potential predators of the species, was monitored using 31 camera traps, distributed among habitats. The FM and the FS are the habitats with greater height of canopy and ground cover rate at FRF, in addition to having a pattern of relatively continuous availability of fruit throughout the year. The areas of RE and MT, in turn, are the habitats with the highest dominance indexes in the plant community, as well as the most open and seasonal ones. From a sampling effort of 1,444 trap-day, capuchin monkeys were recorded in 430 videos in 39 separate visits. Nine of the 10 permanent sampling points in FM or FS received visits of the target-species. No record of the presence of monkeys was obtained in MT or RE. We observed that the areas of FM and FS represent preferential habitats for the yellow-breasted capuchins at FRF. This preference is related to the greater height of canopy and ground cover rate of these areas. The advantages conferred by these parameters refer to both the availability of food and support for the locomotion of the primates, and thus, protection against predation. The main threat faced by the population of S. xanthosternos at FRF refers to its limited size, which in turn, stems from the small size and high degree of isolation of the fragment. The presence of several small remaining fragments in the region, however, enables the creation of ecological corridors, which would increase the total area available for the maintenance of the yellow-breasted capuchins, contributing to the conservation of populations of the species in the state.